KOORDINASI PENANGGULANGAN BENCANA PERGERAKAN TANAH DI KABUPATEN PURWAKARTA - Abdurrahman, Muhammad Arif; Sarihati, Tati; Wulandari, Rafih Sri (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
This research is motivated by the not yet optimal Coordination of Land Movement Disaster Management in Purwakarta Regency. Based on the research background, the researcher formulates the problem as follows: How is the Coordination of Land Movement Disaster Management in Purwakarta Regency. The theory used in this research is the coordination principles proposed by Mc. Farland in Handayaningrat with dimensions of coordination through authority, coordination through consensus, coordination through work guidelines, coordination through forums and coordination through conferences. Based on this theoretical approach, the researcher formulates the following proposition: Coordination of Land Movement Disaster Management in Purwakarta Regency will be optimal if it carries out coordination through authority, coordination through consensus, coordination through work guidelines, coordination through forums and coordination through conferences. The research method used is descriptive qualitative research method. Data obtained through literature study, participant observation, in-depth interviews and documentation. The results of this study indicate that the Coordination of Disaster Management on Land Movements in Purwakarta Regency is not optimal